Botswana: Performance testing of beef cattle - Trail, J.C.M.; Rennie, T.W. (1977)
Describes the system of performance testing operating in Botswana & its value for the genetic improvement of beef cattle, examining dif. aspects of data collection, handling, analysis & use within a computerized system, & recording traits such as reproductive performance, growth, viability & mothering ability.